SISTEM PAKAR DIAGNOSIS KERUSAKAN KOMPUTER DAN INTERNET DENGAN CERTAINTY FACTOR BERBASIS WEB - Hendra Liana; Chairisni Lubis (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
The application that I designed is an expert system to diagnose the faulty or error in computer. The two main components of problems that I address are hardware and software. There are two main feature of this expert system, which is consists of development environment and consultation environment. The development environment is made purposely to manage the diagnoses, symptoms, and relations from the problems that user may approach. As in the consultation environment, user can use it by inserting the input into the consultation table which is provided in the program, then the system will calculate the result based on the certainty factor method with forward chaining system. The final result of this application is a view of the symptoms that choosen by user, and display the probability of diagnoses, but only the diagnoses with the biggest certainty factor value will be choosen as a final result, and accompanied by a final solution.